Cara Mengatasi Kecemasan Dental secara Farmakologis dan Non-Farmakologis: Sebuah Tinjauan Literatur: Pharmacologically and Non-Pharmacologically Treating Dental Anxiety: A Review of the Literature - Wijaya, Ayu; Pariati, Pariati; Aminuddin, Andi Muh. Adam; Feblina, Ayu Rahayu (Jurnal Ilmiah Amanah Akademika, 2023)
Introduction: Anxiety is a type of emotional disorder related to unexpected or dangerous situations. The accompanying physiological signs are sweating, increased blood pressure, increased pulse rate, palpitations, dry mouth, diarrhea, muscle tension and hyperventilation. The anxiety experienced by the patient will increase if there is a perception from the patient, namely that the skills or expertise of the dentist who will carry out the tooth extraction procedure is still quite lacking. Aim: Find out how to deal with anxiety and pain pharmacologically and non-pharmacologically. Methods: Literature review using Google Scholar, PubMed, and Clinical Key databases. Results: Articles that were duplicated, had no full text available, and were reviews were excluded, resulting in 32 articles. The titles and abstracts of the articles were analyzed based on their suitability to the topic so 4 articles were obtained. Anxiety and pain examination is used to determine the level of anxiety and pain felt so that appropriate pharmacological and non- pharmacological treatment can be determined. Conclusion: Feelings of fear and anxiety experienced by children and adults in dental services are not a new phenomenon, so a dentist must be able to approach children in order to have positive interactions and create a more interesting atmosphere for visiting the dentist by seeing and understanding aspects -unliked aspects of visiting the dentist.